2020
DOI: 10.3390/nano10020243
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Wall–Mesenchymal Stem Cells Differentiation on 3D Biodegradable Highly Porous CaSi-DCPD Doped Poly (α-hydroxy) Acids Scaffolds for Bone Regeneration

Abstract: Vascularization is a crucial factor when approaching any engineered tissue. Vascular wall-mesenchymal stem cells are an excellent in vitro model to study vascular remodeling due to their strong angiogenic attitude. This study aimed to demonstrate the angiogenic potential of experimental highly porous scaffolds based on polylactic acid (PLA) or poly-e-caprolactone (PCL) doped with calcium silicates (CaSi) and dicalcium phosphate dihydrate (DCPD), namely PLA-10CaSi-10DCPD and PCL-10CaSi-10DCPD, designed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Recently, nano-engineered materials have been widely applied in the areas of drug delivery, biosensing, stem cells, biomedical science, nanotoxicity evaluation, and tissue engineering [3,[10][11][12][13][14][15][16]. For instance, osteoblast and stem cells cultured on nano-scaffold have long slender morphology on adhesion to neighbor cells; however, the cells cultured in solid scaffold have flat and smooth morphology [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nano-engineered materials have been widely applied in the areas of drug delivery, biosensing, stem cells, biomedical science, nanotoxicity evaluation, and tissue engineering [3,[10][11][12][13][14][15][16]. For instance, osteoblast and stem cells cultured on nano-scaffold have long slender morphology on adhesion to neighbor cells; however, the cells cultured in solid scaffold have flat and smooth morphology [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…PHAs are biocompatible materials, which can be processed as a thermoplastic polymer sand and are frequently used in tissue engineering. 58 , 59 In addition, PHAs can be used as a green alternative to acrylic and epoxy resins as substrates for circuits for the development of environmentally friendly electronic devices. 60 We pave the utilization of RS composites on PHBV as a patch of different shapes to be applied on biological substrates with complex geometries.…”
Section: Resultsmentioning
confidence: 99%
“…Biomaterials able to release biologically active ions have been considered a promising strategy for bone regeneration [43][44][45][56][57][58][59][60]. It has been reported that chemical signals from biomaterials can promote the osteogenic differentiation of mesenchymal stem cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…The release of biologically active ions and the formation of a calcium phosphate layer on the surface may affect the behavior and gene expression of hAD-MSCs and trigger their osteogenic commitment. Indeed, calcium and silicon ions released from CaSi demonstrated to stimulate mineralizing cells proliferation [43][44][45]47,[56][57][58][59][60] enhancing the expression of several genes, such as pro-osteogenic genes (as osteocalcin, bone sialoprotein and alkaline phosphatase) [42][43][44][45][77][78][79] and pro-angiogenic genes [60]. PLA-based CaSi-DCPD-doped scaffolds revealed the ability to support the growth of vascular wall mesenchymal stem cells, stimulating the gene expression of several pro-angiogenic markers, including platelet-derived growth factor receptor-β (PDGFR-β), alpha smooth muscle actin (α-SMA), neuron-glial antigen 2 (NG2), and CD 90 [60].…”
Section: Discussionmentioning
confidence: 99%